HABITAT USE AND BREEDING BIOLOGY OF HERONS IN THE RAMSAR WETLANDS OF NORTHERN TUNISIA - A. Nefla; W. Tlili; R. Ouni; S. Nouira (Journal of Animal and Plant Sciences, 2015)
We studied reproduction patterns and habitat use by Herons at Lebna, Chikli and Ichkeul wetlands in Northern Tunisia during 2009 and 2010. The largest number of herons was recorded at Ichkeul after completion of breeding. Cattle Egrets preferred farmlands but also inhabited marshes. However, all other species (Grey Herons, Great White Herons, Little Egrets and Squacco Herons) seemed to be much dependent on marshes and rivers. The distribution of heron species among habitats varied significantly with years and seasons. Variations of reproductive parameters were revealed between sites, biotopes and years. The most successful nesting points were recorded at Ichkeul for both Little and Cattle Egrets. At Chikli breeding parameters were catastrophic. Losses concerned mainly nests built on the ground; those arboreal had a significantly higher reproductive performance. The clutch size of Cattle Egrets varied positively with diameter of nest at Lebna. Also, at Chikli, the height of nest had a significant effect on both initial and final brood size of Little Egrets. Our results stress the need for further protection measures at study sites. For instance, suitable control of water regime through Tinja channel is absolutely necessary to improve the ornithological value of Ichkeul National Park. Also the accessibility to Lebna and Chikli sites should be highly controlled by managers of Tunisian wetlands, especially during the breeding season.
Keywords: Herons; Habitat use; abundance; Reproductive performance; Ichkeul National Park; Lebna dam; Chikli islet; Conservation